Older Adults' Intention to Socially Isolate Once COVID-19 Stay-at-Home Orders Are Replaced With "Safer-at-Home" Public Health Advisories: A Survey of Respondents in Maryland. (November 2020) - Callow, Michael A.; Callow, Daniel D.; Smith, Charles
Background: The Theory of Planned Behavior (TPB) and the Health Belief Model (HBM) were used to examine the opinion and behaviors of older adults regarding Coronavirus Disease 2019 (COVID-19), social distancing practices, stay-at-home orders, and hypothetical public policy messaging strategies.Method: A convenience sample ( N = 242) of adults 60 and older in the state of Maryland took part in an online survey. Respondents filled out questions regarding demographic information, political affiliation, current social distancing behaviors, and TPB and HBM constructs in our proposed model. Linear regression analysis and analysis of covariance (ANCOVA) were conducted to test the model.Results: Attitude toward social isolation was affected by perceived benefits and barriers to social distancing measures, perceived severity of COVID-19, and political affiliation. Behavior intention was influenced by attitude, subjective norms, political affiliation, and messaging strategies.Conclusion: The study provides support for the conceptual model and has public policy implications as authorities begin to lift stay-at-home orders.